Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1523/jneurosci.0263-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Differentiable Processing of Objects, Associations, and Scenes within the Hippocampus

Abstract: The hippocampus is known to be important for a range of cognitive functions, including episodic memory, spatial navigation, and thinking about the future. However, researchers have found it difficult to agree on the exact nature of this brain structure's contribution to cognition. Some theories emphasize the role of the hippocampus in associative processes. Another theory proposes that scene construction is its primary role. To directly compare these accounts of hippocampal function in human males and females,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
110
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 66 publications
17
110
2
Order By: Relevance
“…Multiple elements of our results, however, clearly show that the pre/parasubiculum and subiculum proper have different patterns of FC. Together with the recent observation that even different regions of the pre/parasubiculum may facilitate distinct forms of mental imagery (Dalton et al, 2018), the current findings provide persuasive evidence that neuroimaging investigations of the hippocampus should, at the very least, differentiate between the pre/parasubiculum and the subiculum proper when investigating contributions of this complex region to human cognition. Indeed, Insausti et al (2017) recently suggested that the concept of a 'subicular cortex' may be incorrect considering it combines the differentiable subicular allocortex (comprising 3 layers) and the pre/parasubicular periallocortex (comprising 6 layers).…”
Section: Whole Subfield Analyses -Fc With Cortical Roissupporting
confidence: 67%
See 1 more Smart Citation
“…Multiple elements of our results, however, clearly show that the pre/parasubiculum and subiculum proper have different patterns of FC. Together with the recent observation that even different regions of the pre/parasubiculum may facilitate distinct forms of mental imagery (Dalton et al, 2018), the current findings provide persuasive evidence that neuroimaging investigations of the hippocampus should, at the very least, differentiate between the pre/parasubiculum and the subiculum proper when investigating contributions of this complex region to human cognition. Indeed, Insausti et al (2017) recently suggested that the concept of a 'subicular cortex' may be incorrect considering it combines the differentiable subicular allocortex (comprising 3 layers) and the pre/parasubicular periallocortex (comprising 6 layers).…”
Section: Whole Subfield Analyses -Fc With Cortical Roissupporting
confidence: 67%
“…We have consistently observed a functional cluster in the medial hippocampus which extends across this demarcation point in tasks relating to scene-based cognition (Dalton et al, 2018;Zeidman et al, 2015a,b;Zeidman and Maguire, 2016). Hence, we believe that this portion of the hippocampus may represent a functional module which, when utilising the uncus-based anatomical demarcation point, would potentially be split between two separate ROIs.…”
Section: Segmentation Of Hippocampal Subfieldsmentioning
confidence: 57%
“…Recent theories of the hippocampus suggest that it performs general-purpose computations independent of stimulus contents (20). Alternatively, it has been suggested that the nature of stimuli, especially their complexity, is a crucial factor in determining whether hippocampus and MTL are involved in a given perceptual task (31,42). The current study addresses these hypotheses by revealing that predictions about complex shapes and simple grating orientations evoked qualitatively different representations in the hippocampus.…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with our results, Webb et al () investigated subsequent memory effects for objects that were encoded either in congruent or incongruent scenes and found increased aHPC activation for schema‐related recollection. Human fMRI studies have also suggested that activation in the aHPC is associated with constructing mental representations of scenes (Dalton, Zeidman, McCormick, & Maguire, ; Zeidman & Maguire, ). Taken together, the results support our hypothesis that the schematic context can be used to facilitate retrieving schema‐related information, and the anterior hippocampus is involved in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Human fMRI studies have also suggested that activation in the aHPC is associated with constructing mental representations of scenes (Dalton, Zeidman, McCormick, & Maguire, 2018;Zeidman & Maguire, 2016).…”
Section: Hippocampus In Schema-related Memory Retrievalmentioning
confidence: 99%